Comparison of Central Corneal Thickness and Lamina Cribrosa Thickness in Ethnic Indians and Ethnic Malays as Predictors of Glaucomatous Optic Neuropathy - Meironi Waimir; Andrini Ariesti; Ardizal Rahman (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Background: Glaucoma poses a public health problem because it is the second leading cause of blindness after cataracts. A thinner central corneal thickness (CCT) is also a contributor to the development of primary open-angle glaucoma (POAG). Lamina cribrosa (LC) is a structure of the optic nerve head (ONH). LC structural changes such as thinning, posterior displacement, and connective tissue deficiency are associated with the mechanism of retinal nerve fiber layer (RNFL) thickness damage, leading to glaucomatous optic neuropathy. Methods: Cross-sectional analytic observational study. A total of 36 eyes from 36 research subjects participated in this study. Data analysis was carried out using SPSS version 25. Then, univariate and bivariate analyzes were carried out to see the difference in CCT and LC thicknesses. Results: The average CCT in ethnic Indians is 514.33 ± 14,142 μm and in ethnic Malays, 542.06 ± 17,234 μm. In this study, there were differences in the average CCT in Indian ethnicity and Malay ethnicity, which was statistically meaningful with a p-value = 0.000. Conclusion: There are differences in the average central corneal thickness and lamina cribrosa thickness in ethnic Indians compared to ethnic Malays, where the central corneal thickness and lamina cribrosa thickness in ethnic Indians are thinner than ethnic Malays.